A new species of the genus Psammogorgia (Cnidaria: Anthozoa: Octocorallia) from the Hannibal Bank in Pacific Panama - Breedy Shadid, Odalisca (2019)
The octocoral faunas occurring at mesophotic depths (from 40 to 150 m) have been relatively unexplored. Recent expeditions to Hannibal Bank, a guyot seamount off Pacific Panama, have yielded new octocoral species and new records for the tropical eastern Pacific. Herein, we describe a new species for the genus Psammogorgia Verrill, 1868a, Psammogorgia pax sp. nov., characterized by having a whitish flabellate colony with orange polyp apertures, slightly raised and sparse calyces, and colorless coenenchymal sclerites (which are mostly spindles and large wart-clubs). A preliminary molecular phylogenetic analysis supports the differences between the new species with other congener and related taxa.